A gravity and magnetic study of lithospheric architecture and structures of South China with implications for the distribution of plutons and mineral systems of the main metallogenic belts. (November 2021) - Yan, Jiayong; Lü, Qingtian; Luo, Fan; Cheng, Shaobo; Zhang, Kun; Zhang, Yongqian; Xu, Yao; Zhang, Chong; Liu, Zhendong; Ruan, Shuai; Wang, Xu
Graphical abstract: Highlights: 3D density and susceptibility models of South China were inverted by gravity and magnetic data. Lithospheric structure such as Moho of South China has been calculated and interpreted. 5 source zones as well as pathways of mineral systems are clearly revealed. Termination sites of mineral system are uncovered by 3D density and susceptibility models. Abstract: South China is characterized by enormous volumes of igneous rocks generated by multiple stages of magmatism. Five large-scale metallogenic belts with many world-class deposits have been discovered, demonstrating great potential for prospecting new resources. To restrict the South China metallogenic cognition the main problems include the types and metal associations of the deposits, factors controlling the distribution of the different types of metallogenic belts, and targets for new deposits. To find possible and feasible solutions to solve these problems. It is necessary to consider the metallogenic factors from the concept of mineral systems. This study first converted the satellite gravity into Bouguer gravity under spherical coordinates. Then the reduction-to-the pole (RTP) magnetic anomalies were obtained using a moving window with different geomagnetic parameters. The vertical lithospheric interfaces and main faults were inverted and interpreted according to these gravity and magnetic data. Based on the results obtained, we have discussed the possible sources and pathways of the five metallogenic belts in South China. Meanwhile, it identified the 3D spatial distribution of intrusions qualitatively by inverted susceptibility and density model, and predicted the potential sites for Cu, Fe, Au, W, and Sn deposits.